Coronary Endarterectomy or Patch Angioplasty for Diffuse Left Anterior Descending Artery Disease - Bitan, Ohad; Pirundini, Paul A.; Leshem, Eyal; Consalvi, Carrie; McGurk, Siobhan; King, Quincy; Loberman, Dan (The Thoracic and Cardiovascular Surgeon, 2018)
Background Coronary endarterectomy and patch angioplasty for the left anterior descending (LAD) artery have been shown to be effective adjunct techniques to surgical revascularization for severe coronary lesions. The objective of this study is to review the short- and long-term results of these two methods in our institution.Methods We retrospectively reviewed 166 consecutive patients who underwent internal thoracic artery grafting to the LAD, with either adjunct endarterectomy (95 patients) or patch angioplasty (71 patients) between 2002 and 2014. We compared the early and late outcomes between groups.Results The endarterectomy patients were older than the patch angioplasty patients (71 vs. 67 years, p = 0.007) and had lower rates of recent myocardial infarction (25% vs. 45%, respectively, p = 0.008). Median pulmonary bypass times and aortic cross clamp times were significantly longer in the endarterectomy group compared with the patch angioplasty group by 47 minutes (p < 0.001) and 42 minutes (p < 0.001), respectively. Median follow-up time was 6.9 years. No significant differences in operative mortality, perioperative myocardial infarction, and long-term survival were found. Freedom from percutaneous coronary intervention at 1 and 5 years was significantly higher in the endarterectomy group compared with the patch angioplasty group (p = 0.002).Conclusions Endarterectomy and patch angioplasty are comparable methods to reach complete revascularization for highly selected patients with diffuse atherosclerotic disease in the LAD. Compared with patch angioplasty, complete extraction of the atherosclerotic plaque with an endarterectomy leads to similar short-term outcomes and long-term survival while significantly reducing the need for further interventions in the future.
Keywords: coronary artery bypass graft surgery; coronary artery bypass grafting; endovascular procedures/stents; outcomes including mortality; morbidity